Current state of the application of artificial intelligence in reliability and maintenance - Pokorni, Slavko J. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: At the end of 2019, the Government of the Republic of Serbia adopted the Strategy for the Development of Artificial Intelligence in the Republic of Serbia for the 2020-2025 period. This was a motivation for the author of this paper to try to give an overview of the current artificial intelligence (AI) applications in the field of reliability and maintenance, as well as its future applications. Methods: The overview is done mainly using available literature, mostly from the Science Direct database, using abstracts generally, and in some cases whole papers. Results: The result of this research is an overview of the artificial intelligence applications in the field of reliability and maintenance in the past thirty years. It also showed that AI systems can also be unreliable and need maintenance. Conclusion: Artificial intelligence is and can be applied in reliability and maintenance. The research of available literature showed that AI is more applied in maintenance than in reliability. The progress in AI is inevitable, so it is important to understand its potentials for application in reliability and maintenance as well as its possible drawbacks.